‘Better active today than radioactive tomorrow!’ : transnational opposition to nuclear energy in France and West Germany, 1968-1981 - Tompkins, A (2013)
This thesis examines the opposition to civil nuclear energy in France and West Germany during the 1970s, arguing that small-scale interactions among its diverse participants led to broad changes in their personal lives and political environments. Drawing extensively on oral history interviews with former activists as well as police reports, media coverage and protest ephemera, this thesis shows how individuals at the grassroots built up a movement that transcended national (and social) borders. They were able to do so in part because nuclear power was such a multivalent symbol at the time. Residents of towns near planned power stations felt that nuclear technology represented an intervention in their community by state and industry, a potential threat to their health, wealth and way of life. In the decade after 1968, concerns like these coalesced with criticisms of capitalism, the state, militarism and consumer society that were being made by a more politicised constituency. This made the anti-nuclear movement both broad-based and highly fragmented. Activist networks linked people across existing national, political and social boundaries, but the social world of activism was subject to its own divisions (such as between locals and outsiders or between militant and non-violent activists). By analysing both the transnational dimensions and internal divisions of the anti-nuclear movement, this thesis revises the homogenising concepts of social movements that are prevalent in much of the existing sociological and political science literature. At the same time, it situates the anti-nuclear movement historically within the decade of upheaval that was the 1970s, while moving individual activists from the margins to the centre of protest history.